Pengaruh Pengetahuan Kesadaran Dan Motivasi Terhadap Keputusan Investasi Mahasiswa Di Universitas Dharma Andalas - Anes Hendry Mendrofa; Ingra Sovita (Jurnal Akuntansi Keuangan dan Bisnis, 2026)
This study aims to analyze the influence of knowledge, awareness, and motivation on student investment decisions at Dharma Andalas University. This research was motivated by the phenomenon of low student investment participation despite the support of the BEI Investment Gallery, where data shows that only 11.85% of students are registered as investors.The research method used was a quantitative associative causal approach. The study sample consisted of 300 respondents drawn through purposive sampling from a total population of 2,160 students. Data were collected using a Likert-scale questionnaire and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) using SmartPLS software.The results showed that, partially, the variables knowledge (t = 6.618), awareness (t = 8.123), and motivation (t = 7.202) had a positive and significant effect on student investment decisions with a p value < 0.05. Simultaneously, the R-Square value of 0.720 indicates that these three variables can explain 72% of the variation in investment decisions. The conclusion of this study confirms that improving literacy and motivation are crucial in strengthening students' financial independence. Institutions are advised to optimize the role of the Investment Gallery through more intensive technical training.